Heavy metal contamination in medicinal plants: assessing carcinogenic and non-carcinogenic health risks - Mohammad Bashir Sulaiman; Auwal M. Adamu; Sulaiman Babayo Ali; Uzoamaka Virginia Ezenobi; Abdullahi Muhammad Gimba; Oluyinka Omoyeni Akinlotan; Auwal Abubakar (Discover Environment, 2024)
Abstract Medicinal plants have played an undeniable role in treating diseases in mankind. However, these plants may be contaminated by toxic substances like heavy metals. Therefore, this study aimed to determine the contamination and health risks (carcinogenic and non-carcinogenic) of heavy metals in economically important medicinal plants mostly in Northern Nigeria. A total of 72 samples from 12 medical plants were purchased and analyzed for heavy metal (Pb, Cr, As, Cd, Zn, Cu, Ni and Fe) contamination using Atomic Absorption Spectrometry (AAS) after wet digestion. The concentrations of the heavy metals (mg·kg−1) were in the range of 1.71–9.01 for Pb, 0.23–2.08 for Cr, 0.00–0.05 for As, 0.00–0.51 for Cd, 5.08–23.67 for Zn, 1.28–13.45 for Cu, 0.96–1.95 for Ni and 20.58–108.50 for Fe. The results revealed that the plant under study contained unsafe levels of Cr and Cd being higher than the World Health Organization (WHO) permissible limits. The hazard index (HI) was < 1, suggesting a probable non-carcinogenic effect. Similarly, the cancer risk (CR) for children and adults was below the (1.0 × 10–4) acceptable limit, indicating non-probable cancer development for consumers. Based on the studied results, the samples may not pose a carcinogenic health risk. However, there is a need for the regulatory agency to continuously monitor medicine plants available in the markets for the safety of consumers.